HUBUNGAN ANTARA PENGETAHUAN KEPALA SEKOLAH TENTANG MANAJEMEN DENGAN PERILAKU ADMINISTRATIF MTsPERKEMAS TELUK BETUNG BANDAR LAMPUNG - Hujaimatul Fauziah (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2013)
In exercising its leadership, the principal must be do the roles and management function likeplanning, organizing, directing, control or suvervison. Management function is the function of mainmanagement.The purpose of this writing is for know the relationship between the principal knowledge asmanagement with administrative behavior principal MTS PerkemasTeluk Betung.The researchresults on the analysis using the descriptive statistic technique and infrasional statistik. Descriptivestatisric are used to examine the hypothesis of reserch results. There is correlation for therelationship between the principal knowledge about management with administrative action with thatlevel of correlation of 0,867 means the correlation between the principal knowledge aboutmanagement will further improve the behavior of principal administrative